Emerging Molecular Links Between Plant Photomorphogenesis and Virus Resistance - Zhai, Ying; Peng, Hao; Neff, Michael M.; Pappu, Hanu R. (Frontiers in Plant Science, 2020)
Photomorphogenesis refers to photoreceptor-mediated morphological changes in plant development that are triggered by light. Multiple photoreceptors and transcription factors (TFs) are involved in the molecular regulation of photomorphogenesis. Likewise, light can also modulate the outcome of plant-virus interactions since both photosynthesis and many viral infection events occur in the chloroplast. Despite the apparent association between photosynthesis and virus infection, little is known about whether there are also interplays between photomorphogenesis and plant virus resistance. Recent research suggests that plant-virus interactions are potentially regulated by several photoreceptors and photomorphogenesis regulators, including phytochromes A and B (PHYA and PHYB), cryptochromes 2 (CRY2), phototropin 2 (PHOT2), the photomorphogenesis repressor Constitutive Photomorphogenesis 1 (COP1), the NAM, ATAF and CUC (NAC)-family TF ATAF2, the Aux/IAA protein PHYTOCHROME-ASSOCIATED PROTEIN 1 (PAP1), the homeodomain-leucine zipper (HD-Zip) TF HAT1, and the core circadian clock component CIRCADIAN CLOCK ASSOCIATED 1 (CCA1). Particularly, the plant growth promoting brassinosteroid (BR) hormones play critical roles in integrating the regulatory pathways of plant photomorphogenesis and viral defense. Here, we summarize the current understanding of molecular mechanisms linking plant photomorphogenesis and defense against viruses, which represents an emerging interdisciplinary research topic in both molecular plant biology and virology.